Mahishasura Mardhini - 88 - Brig Ajai Singh (2022)
Image courtesy: Brig A.P. Singh - www.collectingmoment.in [ Goddess Durga slaying the buffalo demon Mahishasura. The demon can be seen at the Goddess's feet]